2021
DOI: 10.3389/fpsyt.2021.669446
|View full text |Cite
|
Sign up to set email alerts
|

Interest of Fluvoxamine as an Add-On to Clozapine in Children With Severe Psychiatric Disorder According to CYP Polymorphisms: Experience From a Case Series

Abstract: Despite its drastic efficacy in resistant psychiatric disorders, clozapine remains rarely used in youth due to its side effects. Clozapine plasma level is determined through its metabolism involving several isoforms of cytochromes 450 (CYP450) family. Isoform CYP1A2 appears as a limiting enzyme involved in the metabolism of clozapine, while isoforms 2C19, 2D6, 3A4, and 3A5 also contribute in a minor way. Clozapine efficacy is limited by a significant inter-patient variability in exposure according to CYP's pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…In the study of Berel et al [11], the third patient was found to display a CYP2C9*1/*3 heterozygous genotype. Leading to a CYP2C9 IM phenotype, it could partly explain the low clozapine plasma levels.…”
Section: Main Implications Of Cytochromes Genotypingmentioning
confidence: 90%
See 4 more Smart Citations
“…In the study of Berel et al [11], the third patient was found to display a CYP2C9*1/*3 heterozygous genotype. Leading to a CYP2C9 IM phenotype, it could partly explain the low clozapine plasma levels.…”
Section: Main Implications Of Cytochromes Genotypingmentioning
confidence: 90%
“…In the case series of Berel et al [11], the second patient presented a CYP2D6 IM phenotype and a CYP3A5 *1/*1 polymorphism, and these profiles could have contributed to previous high aripiprazole and low haloperidol plasma levels.…”
Section: Main Implications Of Cytochromes Genotypingmentioning
confidence: 92%
See 3 more Smart Citations